Juridical Study Of Food Criminal Action Based On Law Of The Republic Of Indonesia No.18 Of 2012 - I Dewa Gede Ngurah Sena Agung; M. Nurananta Tirta Putra; Moh. Fathoni Cholil; Abdul Faqih Jauhari Pakro (LEGAL BRIEF, 2022)
This study aims to analyze the juridical study of food crimes based on the Republic of Indonesia Law no. 18 of 2012. This study uses a normative approach. The form of this research is descriptive. The method of data collection in this study is to collect secondary data. Secondary data obtained by using literature study. The results showed that the responsibility of business actors in the event of losses to food products that have been marketed to consumers is absolutely responsible for losses that have been received by consumers, ranging from health problems or death due to consuming food or beverage products that are dangerous or contain chemicals that are harmful to consumers and are not recommended for food ingredients. The compensation in question can be in the form of health care or the provision of compensation to consumers who are harmed or by agreement of the parties themselves. As a follow-up to supervision, the government is also authorized to take administrative actions as contained in Article 102 paragraph (3) of the Food Law in the form of fines, temporary cessation of activities, production, and/or distribution, withdrawal of Food from circulation by producers, compensation, and revocation of permits.